Egological meets ecological: Drawing aspects in perspective(s). Issue 2 (1st December 2021) - Riley, Howard; Newell, Robert
Aspects of Edmund Husserl's Egological phenomenology and James J. Gibson's ecological visual perception theory are construed dialectically for the purpose of informing the teaching of drawing, with an emphasis on understanding relationships between viewer positions and objects in the environment as represented through geometric projection systems. Such a grounding is conducive to a drawing practice capable of insights leading to new knowledge of our relationships with our environment, both egological and ecological, in an art school curriculum currently distorted by neo-liberal trends from the core study of visual perception and communication.